Financial distress in Indian Banking Sector due to CoVid-19 (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
At present, the world is suffering due to the hardships caused by the CoVid-19 pandemic. While some countries are battling the 4th wave of CoVid-19, India still awaits the 3rd wave of CoVid-19. The pandemic has led Indian banking sector towards a crisis whose effects are going to be long lasting. Our government took various steps like PM’s Care Fund, moratorium offered by RBI, other measures for small/medium enterprises in order to minimize the ill effects of the crisis caused by the deadly virus. The question here arises is that whether these measures have actually cured the problems are or they just a partial cover. No one knows how is the economy going to behave in coming few years as no actual cure for the virus is yet formulated, medicines are being made, people are being vaccinated but there no evidence as to how beneficial will these medications be against the coming waves of the virus. The current paper examines what hazards has the CoVid-19 pandemic caused in the Indian banking sector with respect to the buildup of NPAs. The study is based on various secondary sources of data and the paper is conceptual in nature.